EFFECT OF ORGANONITROFOS FERTILIZER CONCENTRATION ON THE GROWTH AND PRODUCTION OF ORGANIC TOMATO (Lycopersicon esculentum Mill)WITH SUB SURFACE IRRIGATION SYSTEM - Sayu Putu Okta Rinasari (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2015)
This study aims to observe the effect of concentration of organitrofos fertilizer on the growth and productivity of organic tomato plants with sub irrigation systems. The method used in the study was completely randomized design  with six treatments. The six treatments were O0 (without organonitrofos), O1 (organonitrofos 10%, soil 90%), O2 (organonitrofos 20%, soil 80%), O3 (organonitrofos 30 %, soil 70%), O4 (organonitrofos 40%, soil 60%), and O5 (organonitrofos 50%, soil 50%). The results showed that different concentrations of organonitrofos fertilizer had no effect on the vegetative phase, but sinificantly different on the generative phase, yields, biomase, and evapotranspiration. Based on analysis of LSD, treatment ofO2 ( 20 % organonitrofos, soil 80 % ) was able to significantly increase crop yields compared with the treatments of O0 (without organonitrofos with additional chemical fertilizer ) and treatment O1treatment ( 10 % organonitrofos , soil 90 % ).  But the use of  higher than that in the treatment of O2 ( 20 % organonitrofos, soil 80 % ) did’t significantly increase production. Keywords: Organic Farming, Organonitrofos, Tomato, Subs Irrigation